2019
DOI: 10.1002/rnc.4549
|View full text |Cite
|
Sign up to set email alerts
|

Finite‐time boundedness of large‐scale systems with actuator faults and gain fluctuations

Abstract: Summary This paper addresses the issue of finite‐time boundedness of large‐scale interconnected systems with the use of a distributed nonfragile fault‐tolerant controller. The objective of this paper is to design a state‐feedback controller consisting of a time‐varying delay such that the resulting closed‐loop system is finite‐time bounded under a prescribed extended passivity performance level even in the presence of all admissible uncertainties and possible actuator faults. More precisely, based on the Lyapu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Assumption Refer to References 21 34, we assume that the system state x ( t ) will not jump at the switching time. It means that the track of the system state x ( t ) is continuous.…”
Section: System Description and Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Assumption Refer to References 21 34, we assume that the system state x ( t ) will not jump at the switching time. It means that the track of the system state x ( t ) is continuous.…”
Section: System Description and Preliminariesmentioning
confidence: 99%
“…For the short‐time control problem, Dorato has done the pioneering work 19 . Meanwhile, the issues of finite‐time stability (FTS) and FTB have also been extensively studied by researchers 20-24 . In recent years, the concept of FTS and FTB have also extended to SMC procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of these problems, there are few research results reported for FTS of large-scale systems with delay. We can mention Tharanidharan et al (2019) and La-inchua et al (2017), where the authors proposed sufficient conditions for FTS for a class of linear large-scale systems.…”
Section: Introductionmentioning
confidence: 99%